Determinan Profitabilitas Bank Umum Konvensional Terdaftar di Bursa Efek Indonesia - Bambang Sutrisno (Esensi: Jurnal Bisnis dan Manajemen, 2018)
The Determinant of Profitability in Conventional Commercial Banks Listed in Indonesian Stock ExchangeA lot of prior studies examined the determinants of banks’ profitability, both in developed and developing countries. This paper aims to investigate factors affecting the profitability of 30 commercial banks listed on the Indonesia Stock Exchange (IDX) from 2012 to 2016. This study employs panel regression with annual data. The results reveal that the capital adequacy ratio, net interest margin, and gross domestic product have the positive and significant effect on return on assets. Operating expenses to operating revenues have the negative and significant impact on return on assets. The non-performing loan, loan to deposit ratio, and inflation do not affect return on assets.DOI: 10.15408/ess.v8i1.6554